Moral reasoning at work : rethinking ethics in organizations (2019)
This book explores how ethics in organization can draw on research streams in moral philosophy and moral psychology in order to attune to the actual and concrete moral dilemmas in the workplace. Compliance activities in organizations often include ethical training of employees and formulations of codes of conduct to define required and expected behavior. In order to prepare leaders and employees for moral dilemmas in their professional lives, organizations need to go beyond compliance and acknowledge the complexity and ambiguity of the situations the employees can face. Familiarity with ethical tools, principles, and concepts can be part of a foundation for responsible decision-making, but only in tandem with empirical knowledge from social and moral psychology about judgment and decision-making.